High efficiency water evaporation and purification performance of three-dimensional porous graphene oxide based photothermal evaporators - Qiao Wu; Saihong Ru; Mengxin Wang; Xiaoyu Zheng; Hao Cheng; Maoqing Fan; Wang Li (Chemical Engineering Journal, 2026)

Different mucosal immunity and hormonal responses to routine physical training in the follicular and the luteal phases of elite female athletes - Chung-Kai Wang; Cheng-Shiun He; Ming-Ru Chiang; Pei-Ying Li; Chun-Wei Wang; Liang-You Chen; Shih-Hua Fang (European Journal of Applied Physiology, 2026)

Cadmium disrupts the immune antibacterial function of the freshwater crab Sinopotamon henanense via the Toll/proPO-AS pathway - Yue Liang; Duwen Pei; Cheng Liu; Fenjun Yan; Minnan Bao; Na Liu; Qian Wang; Caiping Feng; Ru Jia; Lan Wang (Journal of Hazardous Materials, 2026)

Two stages of Sn enrichment in granitic magmatism: insights from Sn isotopes of cogenetic minerals - Jia-Xin She; Weiqiang Li; Ru-Cheng Wang; Lei Xie; Chen Liu; Zhihao Xu; Shichao An; Cheng Xu (Geochimica et Cosmochimica Acta, 2026)

Numerical and experimental study on the soot formation in methane multi-jet flames under microgravity - Wen-Jiao Wang; Kai-Ru Jin; Zhi-Hao Zheng; Hong-Qing Shi; Du Wang; Ling-Nan Wu; Ya-Wen Liu; Longfei Li; Jiayu Sun; Yu Cheng Liu; Zhen-Yu Tian (Fuel, 2026)

Non-enzymatic electrochemical determination of the food-related biogenic amine serotonin using a reduced graphene oxide/organic–inorganic Copper(I) phosphate composite - Asit Kumar Panda; Tzu-Yuan Sung; Wan-Ju Lu; Yi-Ru Cheng; Wen-Hui Fang; Chih-Min Wang (Food Bioscience, 2026)

Constructing compatible LLZTO/PEO interfaces with fast Li+ transport channels for high-performance composite polymer electrolytes - Yimei Jin; Yiting Lin; Zekai Zhang; Bing Li; Ru Wang; Cheng Lian; Xia Han; Honglai Liu; Haiping Su; Jingkun Li (Chemical Engineering Journal, 2026)

Brain Serotonin Deficiency Impairs Ovarian Reserve Function via the Hypothalamic-Pituitary-Ovarian Axis - Shuang-Shuang Cui; Zhuo-Nan Yang; Jin Xiao; Jin-Ping Qiao; Yue-Ming Zhang; Ling-Ge Shi; Hui-Ru Cheng; Si-Min Ding; Meng-Yao Wang; Dong-Mei Ji; Tao Zhang; Dan Liang; et al. (Neuroscience Bulletin, 2026)

Multiprotein-based nanomedicines with dual CD44/CD133 targeting and GSH-responsive drug release for improving cancer chemotherapy - Lu-Yi Yu; Pei-Wei Shueng; Yu-Hsin Wang; Yu-Wei Yen; Kuan-Wei Chen; Chieh-Ru Li; Hsin-Cheng Chiu; Yu-Wen Lin; Chun-Liang Lo (Drug Delivery and Translational Research, 2026)
Albumin, a highly biocompatible protein, has been utilized in the construction of anti-cancer drugs for the treatment of various cancers. However, albumin-based nanomedicines still face several clinical challenges, including low stability in the bloodstream, non-specific targeting ability, and lack of controlled release capability. To address these limitations, we developed a multiprotein-based nanomedicine for targeted chemotherapy of non-small cell lung cancer (NSCLC). This nanomedicine was assembled using a heart-shaped albumin and two Y-shaped anti-CD44 and anti-CD133 antibodies. To enhance stability and improve therapeutic efficacy, the multiproteins were crosslinked using disulfide bond linkers and loaded with paclitaxel and ceramide. This resulted in nanomedicines that exhibited responsiveness to glutathione (GSH) and demonstrated inhibition of tumor cancer cells and cancer stem cells (CSCs). Our experimental results indicated that the inclusion of anti-CD44 and anti-CD133 antibodies enhanced the targeting capability of nanomedicines towards cancer cells and CSCs in an in vitro study and the accumulation in both normoxic regions and hypoxic niches in in vivo tumor xenografts. The multiprotein-based nanomedicines also demonstrated GSH-dependent drug release behavior, induced apoptosis in cancer cells and CSCs, inhibited cell migration, and effectively suppressed NSCLC tumor growth. Overall, our findings presented a novel nanostructure created from differently shaped proteins for application in drug delivery. This multiprotein-based nanomedicines showed promising potential in addressing the limitations of albumin-based nanomedicines and may offer improved therapeutic outcomes for cancer treatment. Graphical Abstract

Single-cell transcriptomics reveal PRRC1 as a malignant cell enriched driver of DNA repair and therapy resistance in glioblastoma - Sachin Kumar; Ming-Cheng Tsai; Dahlak Daniel Solomon; Juan Lorell Ngadio; Do Thi Minh Xuan; Ching-Chung Ko; Hung-Yun Lin; Meng-Chi Yen; I-Jeng Yeh; Yung-Kuo Lee; Hui-Ru Lin; Jian-Ying Chuang; et al. (DNA Repair, 2026)

Distinguishing the contributions of organic matter and iron (oxyhydr)oxides to zinc availability in paddy soils surrounding lead-zinc mines - Yecheng Li; Zebin Hong; Yan Ru; Guojun Chen; Xiaomin Li; Shiwen Hu; Yang Yang; Chao Guo; Shan Wang; Pengfei Cheng; Qi Wang; Tongxu Liu (Environmental Pollution, 2026)

Long-term intercropping increases soil aggregate stability by altering soil colloid content and stability - Chuan-Lin Xiao; Jing-Ru He; Cheng-Bao Wang; Wei-Ping Zhang; Jun Mao; Peter Christie; Jian-Ying Shang; Long Li (Plant and Soil, 2026)

Triterpenoids from Ganoderma angustisporum and their α -glucosidase inhibitory activities - Fan-Ru Xu; Le Zhou; Yu-Cheng Dai; Hai-Sheng Yuan; Yu-Xi Wang (Natural Product Research, 2026)

The role of artificial intelligence in advancing population-based cancer registration - Shuai Ding; Mingyuan Liu; Hao Wang; Cheng Song; Luyue Zhao; Zhihao Yang; Yue Wang; Yifan Wang; Haitao Cui; Zihao Liu; Dongrun Liu; Tomohiro Matsuda; et al. (Science Bulletin, 2026)

Recyclable Na-Mn-O nanocomposite for dual-modal photothermal/ROS antibacterial therapy against multidrug-resistant bacteria in pathogen-laden wastewater - Zhi-ru Tao; Shu-xian Hou; Yi-mei Wang; Xue-chao Shi; Xin-xin Liu; Jun Ge; Yu-han Ji; Ya-qi Cheng; Zi-yi Leng; Xin-yv Cao; Rong-rong Li; Jin-nan Xuan; et al. (Journal of Water Process Engineering, 2026)

Tree of life and conservation of gymnosperms in China - Chang-Wang Ma; Dan Xie; Hong Du; Kai-Yuan Huang; Yuan-Yuan Feng; Zhou-Rui Wei; Xin-Quan Liu; Cheng-Ru Li; Jing-Jing Sun; Xiao-Xin Wei; Zhi-Heng Wang; Wei-Hua Xu; et al. (Science China Life Sciences, 2026)

Spatio-seasonal distribution, precursor transformation, and ecological risks of per- and polyfluoroalkyl substances in port sediments: Insights from a subtropical urban harbor - Chih-Feng Chen; Noralyn G. Dimaongon; Yun-Ru Ju; Chiu-Wen Chen; Yee Cheng Lim; Ming-Huang Wang; Cheng-Di Dong (Regional Studies in Marine Science, 2026)

Integrated assessment of trace element enrichment and accumulation in estuarine sediments of southwestern Taiwan using Sr/Ba ratios and pollution indices - Chih-Feng Chen; Noralyn G. Dimaongon; Yee Cheng Lim; Ming-Huang Wang; Yun-Ru Ju; Kent Naiah D. Araña; Chiu-Wen Chen; Cheng-Di Dong (Regional Studies in Marine Science, 2026)

Ecological impacts and sustainable development of offshore wind farm pile foundations in the Bodhi Island area - Xiaochen Cheng; Ting Wang; Zhaoming Gao; Xu Wang; Shuai Liu; Yongchao Hu; Beini Deng; Libin Zhang; Xiaoshang Ru (Marine Environmental Research, 2026)

A dramatic drop in Nb solubility during fractional crystallization of carbonatites triggers Nb ore formation - Ya-Ting Xu; Ru-Cheng Wang; Xu-Dong Che; Fabrice Gaillard; Marion Louvel; Giada Iacono-Marziano; Johann Tuduri (Geochimica et Cosmochimica Acta, 2026)

Inhibition of the Microglial cGAS-STING Pathway Improves Neurological Deficits and Long-Term Hydrocephalus Symptoms in Mice with Intraventricular Hemorrhage - Hao-Xiang Wang; Hua-Jiang Deng; Kun-Hong Zhong; Zi-Ang Deng; Bao-Cheng Gao; Xin Tang; Yuan-You Li; Ke-Ru Huang; Ai-Ping Tong; Da-Xiong Feng; Liang-Xue Zhou (Molecular Neurobiology, 2026)

Fluorescent aptasensor based on magnetic bead–assisted displacement reaction for monitoring vancomycin in plasma - Cheng-Shiuan Hsieh; Hsu-Yun Tsai; Ting-Chien Tsai; Yang-Chun Wang; Yi-Tung Cheng; Jing-Ru Liou; Meng-Yu Liu; Yen-Ling Chen; Chien-Chin Chen (Analytica Chimica Acta, 2026)

Designing light-guiding carriers in microalgal-bacterial systems: From optimization to integration and development perspectives - Cong-Cong Tang; Jin-Qiao Liu; Yong-Qi Cheng; Ya-Ru Hu; Zhang-Wei He; Wen-Qiong Wang; Zhi-Hua Li; Xiaochang C. Wang; Yu Tian (Chemical Engineering Journal, 2025)

GZR101, a Novel Premixed Insulin for the Treatment of Diabetes Mellitus - Wei Chen; Cheng Cui; Wancai Xing; Yining Zhang; Anshun He; Yue Wang; Yan Huang; Nannan Zhai; Qimin Shi; Fangkai Xue; Yongchun Wang; Jun Zhang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

A Li-ion permeable poly(phenylene ether-ether-sulfone) interphase to address interfacial instability and structural degradation of Ni-rich NCM cathodes in poly(ethylene oxide)-based all-solid-state Li-ion batteries - Cheng-Hung Liao; Yu-Ting Weng; Senthil-Kumar Parthasarathi; Hsi Chen; Shu-Jui Chang; Guan-Yi Liu; Tsung-Yu Yu; Chih-Wen Pao; Ting-Shan Chan; Wei-Tsung Chuang; Chun-Chieh Wang; Ru-Jong Jeng; et al. (Chemical Engineering Journal, 2025)

Unraveling the enrichment mechanisms of U, Re, Se and V in the Bayinqinggeli Deposit, Northern Ordos Basin through in situ mineralogical analysis - Xiao-Wen Hu; Ming-Xing Ling; Jian-Bing Xu; Fei Xia; De-Ru Xu; Ya-Lun Li; Xiao-Yong Yang; Chao Lu; Hua-Ming Li; Zhen-Cheng Li; Long-Hui Wang; Feng Zhang; et al. (Journal of Geochemical Exploration, 2025)

In/S co-decorated SnSe encapsulated in a dual carbon layer for sodium ion storage - Ya Ru Pei; Yong Jin Xia; Lei Ming Wang; Rui Li; Jun Xi Peng; Xue Jing Yang; Jian Li; Chun Cheng Yang; Qing Jiang (Chemical Engineering Journal, 2025)

Nickel complex-bridging to enhance electron transport in covalent organic frameworks for efficient photocatalytic uranium reduction - Xiao-Xing Wang; Rui Zhang; Zhi-Hai Peng; Jing-Wen Gong; En-Min Hu; Cheng-Peng Niu; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Arabidopsis HSFA1b functions as a heat sensor inhibiting OST1-mediated stomatal closure through its adenylate-cyclase activity - Yu Zhang; Ru-Feng Song; Xiao-Yu Hu; Hui Zhou; Wei Wang; Junli Zhang; Xin Zhang; Liu-Mei Li; Su-Ting Wang; Yuwei Song; Fuyou Xiang; Jingjing Xing; et al. (Molecular Plant, 2025)

A programmed Ca2+ nanomodulator by dynamically regulating autophagy and neuroinflammation for Parkinson's disease therapy - Wengui Lu; Chuan Zhang; Yaru Zhang; Ru Xiao; Chaoqi Wei; Fan Zhang; Zhenbao Li; Hewan Xia; Mimi Wan; Zhifei Cheng; Qi Wang (Chemical Engineering Journal, 2025)

Overcoming the bottleneck in one-electron reduction of CO2 with mechanical energy-driven triboelectric plasma-enabled catalysis - Qinglong Ru; Bao Zhang; Sumin Li; Jiao Wang; Wei Jiang; Nannan Liu; Hui Hu; Yongcui Yang; Taifeng Liu; Qianhong Gao; Yifei Zhu; Yu Jia; et al. (Chemical Engineering Journal, 2025)

Endothelial Cell Integrin α6 Regulates Vascular Remodeling Through the PI3K/Akt-eNOS-VEGFA Axis After Stroke - Bing-Qiao Wang; Yang-Ying Duan; Mao Chen; Yu-Fan Ma; Ru Chen; Cheng Huang; Fei Gao; Rui Xu; Chun-Mei Duan (Neuroscience Bulletin, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Transcriptome-Wide Sequencing Identifies Non-Coding RNAs and Their Competing Endogenous RNA Networks During the Stages of pPGCLCs-Induced Differentiation - Zhan-Zhong Qiao; Qiu-Yuan Pang; Chang Xu; Xin-Lei Feng; Ming-Xin Zang; Ping Wang; Ying Zhang; Yong-Chao Liu; Qian-Ru Han; Wei Shen; Wei Ge; Shun-Feng Cheng (Stem Cell Reviews and Reports, 2025)

Identification of major fungal diseases in sorghum and screening of broad-spectrum resistance germplasms in Southwest China - Zhi-Fan Yu; Yam Bahadur Kami; Jing-Yang Xia; Xin-Ya Chang; Jin-Yang Li; Jun-Ru Han; Jun Lin; Yuan-Tao Sun; Li-Cheng Wang; Xian-Lin Ni; Wen-Ming Wang; Ji-Wei Zhang (Physiological and Molecular Plant Pathology, 2025)

Multi-scale characteristics and statistically associated factors of ozone pollution in Hangzhou based on machine learning - Yu-ting He; Tao Ding; Ru Yi; Yuan-yuan Wang; Yi Fu; Cheng-kai Tu; Hong-yan Fang; Jin-ye Li; Ming Zhang (Atmospheric Pollution Research, 2025)

Floated Bi4Ti3O12@MoS2 p-n heterojunction anti-fouling hydrogels for efficient seawater purification - Ying Liu; Bingyan Ni; Ruotong Ru; Linlin Zhang; Hongfei Sun; Jianjun Liao; Cheng Li; Dexin Wang; Xiaodong Zhang; Wei Zhou (Journal of Environmental Chemical Engineering, 2025)

Overcrowded steric engineering of through-space interactions for anti-quenching multi-resonance TADF materials - Ru-Jia Wang; Fan Zheng; Jie Hu; Yu-Lan Wu; Xiao-Long Liu; Jia-Xiong Chen; Longjiang Xing; Qiao-Er Wu; Yanping Huo; Wen-Cheng Chen (Chemical Engineering Journal, 2025)

Poly (sodium acrylate-acrylamide) hydrogels for enrichment and purification of microalgal biomass in an open system: performance optimization and mechanistic analysis - Cong-Cong Tang; Yong-Qi Cheng; Sheng-Long Chen; Ya-Ru Hu; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Journal of Environmental Management, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Is there an association between eye-level greenness and childhood hypertension using street view? Findings from the Seven Northeastern Cities study in China - Huang-Min Yang; Jing-Yao Wang; Cheng Li; Ya-Qin Zhang; Ruoyu Wang; Qi Yang; Yao Yao; Zilong Wang; Shu-Li Xu; He-Hai Huang; Qian-Sheng Hu; Ru-Qing Liu; et al. (Environmental Research, 2025)

Microplastic pollution in stony coral skeletons and tissues: A case study of accumulation and interrelationship in South Penghu Marine National Park, Taiwan Strait - Chih-Feng Chen; Yun-Ru Ju; Ming-Huang Wang; Yee Cheng Lim; Chiu-Wen Chen; Yu-Rong Cheng; Cheng-Di Dong (Journal of Hazardous Materials, 2025)

Effect of vacuum frying on the structure and bioactivity of proanthocyanidins in Chinese quince (Chaenomeles sinensis Koehne) fruit - Yu Lou; Xu Fang; Zi-Cheng Yang; Jia-Lin Fei; Yu-Ru Feng; Zhao Qin; Hua-Min Liu; Yu-Xiang Ma; Xue-De Wang (Food Chemistry, 2025)

Estimating monthly NO2, O3, and SO2 concentrations via an ensemble three-stage procedure with downscaled satellite remote sensing data and ground measurements - Chu-Chih Chen; Yin-Ru Wang; Fu-Cheng Wang; Yi-Shiang Shiu; Chang-Fu Wu; Tang-Huang Lin (Journal of Hazardous Materials, 2024)

PRDX1 Interfering Peptide Disrupts Amino Acids 70–90 of PRDX1 to Inhibit the TLR4/NF-κB Signaling Pathway and Attenuate Neuroinflammation and Ischemic Brain Injury - Xiang-Yu Ma; Cheng-yu Qi; Xing-yi Xu; Hui Li; Chang-Dong Liu; Xiang-Ru Wen; Yan-Yan Fu; Yan Liu; Jia Liang; Cheng-Yu Huang; Dan-Dan Li; Yan Li; et al. (Molecular Neurobiology, 2024)

A review of urinary HPV testing for cervical cancer management and HPV vaccine surveillance: rationale, strategies, and limitations - Lin Cheng; Ru Wang; Jing Yan (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Emergency control of dinoflagellate bloom in freshwater with chlorine enhanced by solar radiation: Efficiency and mechanism - Ru Wang; Ya Cheng; Qiqi Wan; Ruihua Cao; Jie Cai; Tinglin Huang; Gang Wen (Water Research, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

Improved prediction of swimming talent through random forest analysis of anthropometric and physiological phenotypes - Cheng Liu; Bingxiang Xu; Kang Wan; Qin Sun; Ruwen Wang; Yue Feng; Hui Shao; Tiemin Liu; Ru Wang (Phenomics, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Accurate and precise in situ determination of beryllium contents in beryllium minerals using ablation spot size of 13 μm by LA–ICP–MS - Wen-Kai Jin; Xu-Dong Che; Ru-Cheng Wang; Huan Hu; Can Rao; Wen-Lan Zhang; Xiao-Feng Li (Journal of Geochemical Exploration, 2024)

Estimation of linezolid exposure in patients with hepatic impairment using machine learning based on a population pharmacokinetic model - Ru Liao; Lihong Chen; Xiaoliang Cheng; Houli Li; Taotao Wang; Yalin Dong; Haiyan Dong (European Journal of Clinical Pharmacology, 2024)

Asperidulins A and B, two new prenylxanthone derivatives from an apple-derived fungus Aspergillus nidulans KIB-HACM-01 - Peng Lai; Li Wang; Chenjie Deng; Yixin Xu; Xiao-Yan Ma; Chun-Ru Cheng; Sheng-Xiong Huang (Natural Product Research, 2024)

C-Phycocyanin improves the quality of goat oocytes after in vitro maturation and vitrification - Xing-Yue Wang; Yang Gao; Hao-Ran Liu; Teng Wang; Meng-Lei Feng; Fang-Rui Xue; Kang Ding; Qi Yang; Zhao-Yu Jiang; Dui Sun; Chun-Ru Song; Xiao-Jie Zhang; et al. (Theriogenology, 2024)

Phosphorylated covalent organic framework/graphene composites for photoelectrothermal integrated collaborative reduction of uranium - Rui Zhang; Liang Tao; Cheng-Peng Niu; Cheng-Rong Zhang; Tie-Ying Shi; Xiao-Xing Wang; Ying-Ao Wang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Migration of phosphorus in pig manure during pyrolysis process and slow-release mechanism of biochar in hydroponic application - Ru-Qing Jiang; Guang-Wei Yu; Lin-Hui Yu; Yu Wang; Chang-Jiang Li; Zhen-Jiao Xing; Xi-Mei Xue; Yin Wang; Cheng Yu (Science of The Total Environment, 2024)

Unravelling hidden threats of water disinfection: Toxicity evaluation and toxic products identification during diclofenac degradation - Ding Pan; Cheng Zhang; Cai-Shan Wang; Peng Zhang; Xin-Yi Jiao; Qian-Ru Ma; Li-Ting Wang; Dai-Jun Li; Li-Ping Li (Environmental Pollution, 2024)

Formation of lithium-rich pegmatites via rapid crystallization and shearing – case study from the South Tibetan Detachment, Himalaya - Xiao-Chi Liu; Matthew J. Kohn; Jia-Min Wang; Shao-Xiong He; Ru-Cheng Wang; Fu-Yuan Wu (Earth and Planetary Science Letters, 2024)

Inflammation and Brain Structure in Alzheimer’s Disease and Other Neurodegenerative Disorders: a Mendelian Randomization Study - Wei-Shi Liu; Ya-Ru Zhang; Yi-Jun Ge; Hui-Fu Wang; Wei Cheng; Jin-Tai Yu (Molecular Neurobiology, 2024)

Fully space-confined donor-acceptor interaction for highly efficient thermally activated delayed fluorescence emitters - Wen-Cheng Chen; Ming-Hui Zheng; Yu-Lan Wu; Ru-Jia Wang; Jia-Ming Jin; Si-Wei Chen; Bo Liu; Jia-Xiong Chen; Yanping Huo; Shaomin Ji (Chemical Engineering Journal, 2024)

Magmatic–hydrothermal evolution of the Koktokay No. 3 pegmatite, Altai, northwestern China: Constraints from in situ boron isotope and chemical compositions of tourmaline - Rong Yin; Xiao-Long Huang; Ru-Cheng Wang; Gang-Jian Wei; Yi-Gang Xu; Yu Wang; Xiao-Ming Sun; Le Zhang; Xiao-Ping Xia (Lithos, 2023)

Wood frame structured carbons with integrated sieving layer for propylene/propane separation - Cheng-Tong Wang; Wen-Cui Li; Shuang Xu; Ru-Shuai Liu; Guang-Ping Hao; An-Hui Lu (Chemical Engineering Journal, 2023)

Mineralogy, petrology and P-T conditions of the spodumene pegmatites and surrounding meta-sediments in Lhozhag, eastern Himalaya - Jia-Min Wang; Kang-Shi Hou; Lei Yang; Xiao-Chi Liu; Ru-Cheng Wang; Guang-Ming Li; Jian-Gang Fu; Fang-Yang Hu; Yu-Lu Tian; Fu-Yuan Wu (Lithos, 2023)

Dual N-modification enables high-performance Solid-State Li metal batteries with Li5.5PS4.5Cl1.5 - Chaochao Wei; Ru Wang; Zhongkai Wu; Qiyue Luo; Ziling Jiang; Liang Ming; Long Zhang; Hongcheng Lu; Guangshe Li; Liping Li; Chuang Yu; Shijie Cheng (Chemical Engineering Journal, 2023)

Mechanical energy-driven triboelectric plasma catalytic CO2 reduction over oxygen-vacancy-introduced In2O3 nanoparticles - Xiaochen Xiang; Jiao Wang; Qinglong Ru; Sumin Li; Ke Zhao; Yifei Zhu; Zhenpan Chen; Liangliang Liu; Guangqin Gu; Yu Jia; Bao Zhang; Gang Cheng; et al. (Chemical Engineering Journal, 2023)

Microplastics in coastal farmed oyster (Crassostrea angulata) shells: Abundance, characteristics, and diversity - Chih-Feng Chen; Yun-Ru Ju; Yee Cheng Lim; Ming-Huang Wang; Chiu-Wen Chen; Cheng-Di Dong (Marine Pollution Bulletin, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Effect of liver metastasis on the efficacy of immune checkpoint inhibitors in cancer patients: a systemic review and meta-analysis - Bao-Wen Tian; Cheng-Long Han; Han-Chao Wang; Lun-Jie Yan; Zi-Niu Ding; Hui Liu; Xin-Cheng Mao; Jin-Cheng Tian; Jun-Shuai Xue; Long-Shan Yang; Si-Yu Tan; Zhao-Ru Dong; et al. (Clinical & Experimental Metastasis, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

Nonagricultural emissions enhance dimethylamine and modulate urban atmospheric nucleation - Yunhua Chang; Qingyang Ling; Xinlei Ge; Xiangyang Yuan; Shengqian Zhou; Kai Cheng; Jianjiong Mao; Dandan Huang; Qingyao Hu; Jun Lu; Shijie Cui; Yaqing Gao; et al. (Science Bulletin, 2023)

Highly sensitive plasmonic biosensor for hepatitis B virus DNA based on the surface etching of the active helical gold nanorods - Ru Cheng; Liang Tong Li; Min Huang; Fu Zhu; Qian Li; Hui Liu; Jie Gao; Xiao Hui Zhao; Fu Kang Luo; Jian Wang (Chemical Engineering Journal, 2023)

Associations of long-term joint exposure to various ambient air pollutants with all-cause and cause-specific mortality: evidence from a large population-based cohort study - Zhi-Hao Li; Xiao-Meng Wang; Jia-Xuan Xiang; Ying Nan; Ying-Jun Chen; Pei-Dong Zhang; Dan Liu; Dong Shen; Xi-Ru Zhang; Wen-Fang Zhong; Pei-Liang Chen; Qing-Mei Huang; et al. (Environmental Science and Pollution Research, 2023)

Environmental regulation, industrial agglomeration, and marine green development efficiency: an empirical analysis from China’s coastal provinces - Ke-Liang Wang; Xiang-Xiang Ru; Li-Li Ding; Yun-He Cheng (Environmental Science and Pollution Research, 2023)

Ndufa4 Regulates the Proliferation and Apoptosis of Neurons via miR-145a-5p/Homer1/Ccnd2 - Fang Fu; Chen Chen; Kun Du; Lu-shan Li; Ru Li; Ting-ying Lei; Qiong Deng; Dan Wang; Qiu-xia Yu; Xin Yang; Jin Han; Min Pan; et al. (Molecular Neurobiology, 2023)
The Dandy–Walker malformation (DWM) is characterized by neuron dysregulation in embryonic development; however, the regulatory mechanisms associated with it are unclear. This study aimed to investigate the role of NADH dehydrogenase 1 alpha subcomplex 4 (NDUFA4) in regulating downstream signaling cascades and neuronal proliferation and apoptosis. Ndufa4 overexpression promoted the proliferation of neurons and inhibited their apoptosis in vitro, which underwent reverse regulation by the Ndufa4 short hairpin RNAs. Ndufa4 -knockout (KO) mice showed abnormal histological alterations in the brain tissue, in addition to impaired spatial learning capacity and exploratory activity. Ndufa4 depletion altered the microRNA expressional profiles of the cerebellum: Ndufa4 inhibited miR-145a-5p expression both in the cerebellum and neurons. miR-145a-5p inhibited the proliferation of neurons and promoted their apoptosis. Ndufa4 promoted and miR-145a-5p inhibited the expression of human homer protein homolog 1 and cyclin D2 in neurons. Thus, Ndufa4 promotes the proliferation of neurons and inhibits their apoptosis by inhibiting miR-145a-5p, which directly targets and inhibits the untranslated regions of Homer1 and Ccnd2 expression.

Prenatal diagnosis in the fetal hyperechogenic kidneys: assessment using chromosomal microarray analysis and exome sequencing - Ruibin Huang; Fang Fu; Hang Zhou; Lu Zhang; Tingying Lei; Ken Cheng; Shujuan Yan; Fei Guo; You Wang; Chunling Ma; Ru Li; Qiuxia Yu; et al. (Human Genetics, 2023)

Electrochemical etching induced high-valence cobalt with defects site for boosting electrochemical water splitting - Hongmei Gao; Jiaqi Liu; Zijin Zhang; Yuxuan Lu; Ru Chen; Yu-Cheng Huang; Chao Xie; Mengyi Qiu; Tianyu Wu; Jinbo Wang; Yubin Jiang; Chung-Li Dong; et al. (Chemical Engineering Journal, 2023)

Circulating polyunsaturated fatty acids, fish oil supplementation, and risk of incident dementia: a prospective cohort study of 440,750 participants - Yu He; Shu-Yi Huang; Hui-Fu Wang; Wei Zhang; Yue-Ting Deng; Ya-Ru Zhang; Qiang Dong; Jian-Feng Feng; Wei Cheng; Jin-Tai Yu (GeroScience, 2023)

mRNA 3ʹ -UTR-mediate translational control through PAS and CPE in sheep oocyte - Chun-Ru Song; Ru-Jing Zhang; Fang-Rui Xue; Xiao-Jie Zhang; Xing-Yue Wang; Dui Sun; Kang Ding; Qi Yang; Xin-Yu Wang; Cheng-Guang Liang (Theriogenology, 2023)

Extraction of weak hydrophobic sulforaphane from broccoli by salting-out assisted hydrophobic deep eutectic solvent extraction - Wen-wen Deng; Xue-ping Mei; Zi-jun Cheng; Tian-xiang gan; Xuan Tian; Jiang-nan Hu; Chuan-ru Zang; Bo Sun; Jing Wu; Yin Deng; Reza. A. Ghiladi; George H. Lorimer; et al. (Food Chemistry, 2023)

Self-oxidation cycle of oxidized red phosphorus for regeneration of binding sites enables efficient uranium extraction in tributylphosphate-kerosene system - Yingtong Lv; Ru Cheng; Guolin Yang; Wang Liu; Jingye Zhang; Xiaofang Yu; Wencai Bai; Rong He; Wenkun Zhu (Chemical Engineering Journal, 2023)

Whole exome sequencing improves genetic diagnosis of fetal clubfoot - Ruibin Huang; Hang Zhou; Chunling Ma; Fang Fu; Ken Cheng; You Wang; Ru Li; Tingying Lei; Qiuxia Yu; Dan Wang; Shujuan Yan; Xin Yang; et al. (Human Genetics, 2023)

Restrictions on Niobium enrichment by alteration of Niobium-rich biotite in pure water, acid, alkaline and fluoride-bearing solutions at 200 MPa and 300–600 °C - Zhao-Yu Yang; Ru-Cheng Wang; Xu-Dong Che; Daniel Harlov (Geochimica et Cosmochimica Acta, 2023)

Dissolved organic matter–assisted phytoremediation potential of cotton for Cd-contaminated soil: a relationship between dosage and phytoremediation efficiency - Tao Min; Tong Luo; Hao He; Jie Qin; Yan Wang; Liyang Cheng; Sibo Ru; Junhua Li (Environmental Science and Pollution Research, 2022)

Damage and Failure Characteristics and Constitutive Model of Copper-Bearing Skarns Disturbed by Hierarchical Dynamic Loading After Loading And Unloading - Chun Wang; Jia Li; Lu- ping Cheng; Xin-ru Li; Pan-long Zhang; Man-gu Hu (Rock Mechanics and Rock Engineering, 2022)

A new highly oxygenated germacranolide from Carpesium nepalense var. lanatum (C.B.Clarke) Kitam - Yi-Fan Yu; Yue-Qian Li; Ru-Yue Wang; Xu Liu; Wen-Bo Cui; Xiao-Han Chen; Cheng-Mu Zhao; Feng-Ming Qi; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

Imatinib-induced hepatotoxicity via oxidative stress and activation of NLRP3 inflammasome: an in vitro and in vivo study - Feng-Ru Huang; Wen-Tong Fang; Zi-Ping Cheng; Ye Shen; Dun-Jian Wang; Yong-Qing Wang; Lu-Ning Sun (Archives of Toxicology, 2022)

Synthesis and biological activity of amide derivatives derived from natural product Waltherione F - Hongbin Fang; Zhanfang Chen; Xuewen Hua; Wenrui Liu; Chenmeng Xue; Yi Liu; Xiaohe Zhu; Man Yuan; Shuang Cheng; Bingxiang Wang; Jing Ru; Dzmitry Bazhanau; et al. (Medicinal Chemistry Research, 2022)

Haloterrigena gelatinilytica sp. nov., a new extremely halophilic archaeon isolated from salt-lake - Bing-Bing Liu; Nimaichand Salam; Manik Prabhu Narsing Rao; Shuang Cheng; Yuan-Guo Xie; Lai-You Wang; Yuan-ru Zhang; Xin-Yuan Yu; Shu-xian Guo; Wen-Jun Li (Archives of Microbiology, 2022)

circSVIL regulates bovine myoblast development by inhibiting STAT1 phosphorylation - Binglin Yue; Haiyan Yang; Jiyao Wu; Jian Wang; Wenxiu Ru; Jie Cheng; Yongzheng Huang; Xianyong Lan; Chuzhao Lei; Hong Chen (Science China Life Sciences, 2022)

Transcriptome analysis of differentially expressed genes in chrysanthemum MET1 RNA interference lines - Dong-ru Kang; Yi Zhu; Shuai-lei Li; Peng-hui Ai; Muhammad Ayoub Khan; Hong-xu Ding; Ying Wang; Zi-cheng Wang (Physiology and Molecular Biology of Plants, 2021)

Content and health risk assessment of heavy metals and polybrominated diphenyl ethers in fish from Songhua Lake (Jilin City), China - Mengnan Shen; Chunyu Kang; Tiehong Song; Hai Lu; Yuehong Wang; Bowen Yu; Ru Wang; Jie Cheng (Environmental Science and Pollution Research, 2020)

Liquiritin inhibits proliferation and induces apoptosis in HepG2 hepatocellular carcinoma cells via the ROS-mediated MAPK/AKT/NF-κB signaling pathway - Jia-Ru Wang; Tian-Zhu Li; Cheng Wang; Shu-Mei Li; Ying-Hua Luo; Xian-Ji Piao; Yu-Chao Feng; Yi Zhang; Wan-Ting Xu; Yu Zhang; Tong Zhang; Shi-Nong Wang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

A new phenanthropyran and a new biphenanthrene from the rhizomes of Dioscorea septemloba and their antioxidant activities - Tao He; Yi Liu; Rui-Feng Xiong; Xiao-Yu Li; Shou-Feng Wang; Chun-Ru Cheng (Natural Product Research, 2020)

Quantification of cardiac pumping mechanics in rats by using the elastance–resistance model based solely on the measured left ventricular pressure and cardiac output - Chih-Hsien Wang; Ru-Wen Chang; En-Ting Wu; Chun-Yi Chang; Hsien-Li Kao; Ming-Shiou Wu; Ya-Jung Cheng; Yih-Sharng Chen; Kuo-Chu Chang (Pflügers Archiv - European Journal of Physiology, 2019)

Selenium (Se) Does Not Reduce Cadmium (Cd) Uptake and Translocation in Rice (Oryza sativa L.) in Naturally Occurred Se-Rich Paddy Fields with a High Geological Background of Cd - Bei-Bei Yang; Cheng Yang; Zong-Yuan Shao; Hao Wang; Shu-Ting Zan; Meng Zhu; Shou-Biao Zhou; Ru-Yi Yang (Bulletin of Environmental Contamination and Toxicology, 2019)

Applying the strategy of light environment control to improve the biomass and polysaccharide production of Nostoc flagelliforme - Pei-pei Han; Shi-gang Shen; Hui-Yan Wang; Shun-yu Yao; Zhi-lei Tan; Cheng Zhong; Shi-ru Jia (Journal of Applied Phycology, 2017)

Peripheral Blood MicroRNA Expression Profiles in Alzheimer’s Disease: Screening, Validation, Association with Clinical Phenotype and Implications for Molecular Mechanism - Ru-Jing Ren; Yong-Fang Zhang; Eric B. Dammer; Yi Zhou; Li-ling Wang; Xiao-Hong Liu; Bei-Lei Feng; Guo-Xin Jiang; Sheng-Di Chen; Gang Wang; Qi Cheng (Molecular Neurobiology, 2016)

Sodium Channel Voltage-Gated Beta 2 Plays a Vital Role in Brain Aging Associated with Synaptic Plasticity and Expression of COX5A and FGF-2 - Yan-Bin XiYang; You-Cui Wang; Ya Zhao; Jin Ru; Bing-Tuan Lu; Yue-Ning Zhang; Nai-Chao Wang; Wei-Yan Hu; Jia Liu; Jin-Wei Yang; Zhao-Jun Wang; Chun-Guang Hao; et al. (Molecular Neurobiology, 2016)

Comparison of bacterial community structures of terrestrial cyanobacterium Nostoc flagelliforme in three different regions of China using PCR-DGGE analysis - Pei-pei Han; Shi-gang Shen; Shi-ru Jia; Hui-yan Wang; Cheng Zhong; Zhi-lei Tan; He-xin Lv (World Journal of Microbiology and Biotechnology, 2015)

Geochronological and geochemical constraints on the petrogenesis and geodynamic setting of the Qianlishan granitic pluton, Southeast China - Chun-Li Guo; Ru-Cheng Wang; Shun-Da Yuan; Sheng-Hua Wu; Bing Yin (Mineralogy and Petrology, 2015)

Cell-density-dependent manifestation of partial characteristics for neuronal precursors in a newly established human gliosarcoma cell line - Pei-Sen Yao; De-Zhi Kang; Xing-Fu Wang; Ru-Ying Lin; Zu-Cheng Ye (In Vitro Cellular & Developmental Biology - Animal, 2015)

Two new cytotoxic iridoid esters from the rhizomes and roots of Patrinia heterophylla Bunge - Bo Yang; Ru-Bin Cheng; Yi-Qi Wang; Li Shen; Ru-Song Zhang (Natural Product Research, 2013)

Fine structure and primary sensory projections of sensilla located in the labial-palp pit organ of Helicoverpa armigera (Insecta) - Xin-Cheng Zhao; Qing-Bo Tang; Bente G. Berg; Yang Liu; Yan-Ru Wang; Feng-Ming Yan; Gui-Rong Wang (Cell and Tissue Research, 2013)

Effect of Sulforaphane on Growth Inhibition in Human Brain Malignant Glioma GBM 8401 Cells by Means of Mitochondrial- and MEK/ERK-Mediated Apoptosis Pathway - Tzuu-Yuan Huang; Weng-Cheng Chang; Miin-Yau Wang; Yun-Ru Yang; Yi-Chiang Hsu (Cell Biochemistry and Biophysics, 2012)

Cassiterite exsolution with ilmenite lamellae in magnetite from the Huashan metaluminous tin granite in southern China - Ru Cheng Wang; A-Peng Yu; Jun Chen; Lei Xie; Jian-Jun Lu; Jin-Chu Zhu (Mineralogy and Petrology, 2012)

Polycyclic aromatic hydrocarbons in household dust near diesel transport routes - Chung-Yih Kuo; Heng-Chun Chen; Fang-Ching Cheng; Li-Ru Huang; Po-Shan Chien; Jing-Ya Wang (Environmental Geochemistry and Health, 2012)

Construction and characterization of a normalized cDNA library from the river snail Bellamya aeruginosa after exposure to copper - Zi-Cheng Li; Li-Hui An; Qing Fu; Ying Liu; Lei Zhang; Hao Chen; Xing-Ru Zhao; Li-Jing Wang; Bing-Hui Zheng; Lin-Bo Zhang (Ecotoxicology, 2012)

Reactive oxygen species-mediated PKC and integrin signaling promotes tumor progression of human hepatoma HepG2 - Chi-Tan Hu; Jia-Ru Wu; Chuan-Chu Cheng; Sindy Wang; Hsiao-Ting Wang; Ming-Che Lee; Ling-Jung Wang; Siou-Mei Pan; Tsu-Yao Chang; Wen-Sheng Wu (Clinical & Experimental Metastasis, 2011)

Functional characterization of a plasma membrane Na+/H+ antiporter from alkali grass (Puccinellia tenuiflora) - Xin Wang; Ru Yang; Baichen Wang; Guifeng Liu; Chuanping Yang; Yuxiang Cheng (Molecular Biology Reports, 2011)

Estimation of nested spatial patterns and seasonal variation in the longitudinal distribution of Sicyopterus japonicus in the Datuan Stream, Taiwan by using geostatistical methods - Yu-Pin Lin; Cheng-Long Wang; Chi-Ru Chang; Hsiao-Hsuan Yu (Environmental Monitoring and Assessment, 2011)

IL-6 −174G>C polymorphism and cancer risk: a meta-analysis involving 29,377 cases and 37,739 controls - Bin Xu; Xiao-Bing Niu; Zi-Dun Wang; Wei Cheng; Na Tong; Yuan-Yuan Mi; Zhi-Chao Min; Jun Tao; Peng-Chao Li; Wei Zhang; Hong-Fei Wu; Zheng-Dong Zhang; et al. (Molecular Biology Reports, 2011)

Establishment of a transgene expression system for the marine microalga Schizochytrium by 18S rDNA-targeted homologous recombination - Ru-Bin Cheng; Xiang-Zhi Lin; Zhao-Kai Wang; Shan-Jun Yang; Hui Rong; Yong Ma (World Journal of Microbiology and Biotechnology, 2011)

PTEN status is related to cell proliferation and self-renewal independent of CD133 phenotype in the glioma-initiating cells - Ru-Bin Cheng; Rui-Juan Ma; Zhao-Kai Wang; Shan-Jun Yang; Xiang-Zhi Lin; Hui Rong; Yong Ma (Molecular and Cellular Biochemistry, 2011)

Methylobacterium soli sp. nov. a methanol-utilizing bacterium isolated from the forest soil - Yan-Ru Cao; Qian Wang; Rong-Xian Jin; Shu-Kun Tang; Yi Jiang; Wen-Xiang He; Hang-Xian Lai; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2011)

Rubellimicrobium roseum sp. nov., a Gram-negative bacterium isolated from the forest soil sample - Yan-Ru Cao; Yi Jiang; Qian Wang; Shu-Kun Tang; Wen-Xiang He; Quan-Hong Xue; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2010)

Origin of the Gangdise (Transhimalaya) Permian arc in southern Tibet: Stratigraphic and volcanic geochemical constraints - Quan‐Ru Geng; Zhi‐Ming Sun; Gui‐Tang Pan; Di‐Cheng Zhu; Li‐Quan Wang (Island Arc, 2009)
The well‐studied Mesozoic and Cenozoic volcanic rocks of the Gangdise Terrane, southern Tibet, are widely interpreted to have resulted from subduction of the Neotethys; however, Late Paleozoic volcanic rocks and their tectonic setting remain poorly studied. Based on new geological data, we carried out stratigraphical and geochemical analyses of Permian volcano‐stratigraphic sequences within an east–west‐trending, fault‐bounded zone of uplift in the central Gangdise Terrane. Sedimentary rocks in this area consist of platform carbonates and terrigenous clastic rocks that represent widespread shallow‐marine sedimentary basins developed around northern Gondwana. A regression or tectonic uplift event is recorded in Permian sedimentary rocks that show the local development of fluvial environments. The sedimentary succession contains evidence of two volcanic stages: a period of basaltic extrusions and younger explosive felsic magmatism. The first volcanic stage is Early and Middle Permian in age. Tholeiitic basaltic lavas are exposed around Maizhokunggar (Tangjia) and Lhunzhub in central Gangdise. The Lower Permian basalts are relatively enriched in MgO (4.58–12.19%), whereas the Middle Permian basalts are characterized by high Al 2 O 3 contents (11.75–21.22%). Rocks of both ages are enriched in large‐ion lithophile elements (LILE) and light rare earth elements (LREE), and show pronounced negative Nb and Ta anomalies. Total REE contents and light (LREE)/heavy (HREE) ratios increased from the Early to Middle Permian. Observed variations in initial Sr, Nd, and Pb isotopes ( 87 Sr/ 86 Sr i = 0.7013–0.7066, 207 Pb/ 204 Pb i = 15.53–15.63, and 208 Pb/ 204 Pb i = 38.04–38.64 for a given 206 Pb/ 204 Pb i ; εNd = +0.69 to −11.55) can be explained by crustal interaction with mantle sources, as is characteristic of metasomatism by slab‐derived fluids or assimilation and fractional crystallization (AFC) processes during magmatic evolution. The observed geochemical signatures, coupled with stratigraphic constraints, support the hypothesis that an initial arc formed during the Permian due to southward subduction of the Paleotethys, predating the well‐known Mesozoic arc preserved in the Gangdise Terrane.

Exsolution lamellae in a clinopyroxene megacryst aggregate from Cenozoic basalt, Leizhou Peninsula, South China: petrography and chemical evolution - Xiao-Long Huang; Yi-Gang Xu; Ching-Hua Lo; Ru-Cheng Wang; Chuan-Yong Lin (Contributions to Mineralogy and Petrology, 2007)

Analyzing Hazard Potential of Typhoon Damage by Applying Grey Analytic Hierarchy Process - Szu-Ping Cheng; Ru-Yih Wang (Natural Hazards, 2004)

Analysis of heat-shock protein70 gene polymorphisms and the risk of Parkinson?s disease - Chiung-Mei Chen; Yuying Hsu; Sih-Jing Lin; Kuo-Hsuan Chang; Guey-Jen Lee-Chen; Cheng-Kuang Wang; Yi-Ying Lin; Yih-Ru Wu; Hon-Chung Fung (Human Genetics, 2004)